Jawabanmu

Jawaban paling cerdas!
2014-08-29T21:37:03+07:00
A) 7a²-(-9a²)+5b = 7a²+9a²+5b
                       = 16a²+5b
b) 9a-a²-6a-(-a²) = 9a-a²-6a+a² = 9a-6a-a²+a²
                       = 3a
c) x²-2x-(-3x²)-3+(-x)-9 = x²-2x+3x²-3-x-9 = x²+3x²-2x-x-3-9
                                 = 4x²-3x-12
d) -3ab+5bc-(-2bc)-ab = -3ab+5bc+2bc-ab = -3ab-ab+5bc+2bc
                                = -4ab+7bc
     semoga membantu :)
3 5 3
2014-08-29T22:31:08+07:00
A. 7a² - ( -9a² ) + 5b
    = 7a² + 9a² + 5b
    = 16a² + 5b
b. 9a - a² - 6a - ( -a² )
    = 9a - a² - 6a + a²
    = 9a - 6a - a² + a²
    = 3a
c. x² - 2x - ( -3x² ) - 3 + ( -x ) - 9
    = x² - 2x + 3x² - 3 - x -9
    = x² + 3x² - 2x - x - 3 - 9
    = 4x² - 3x - 12
d. 3ab - 9 + ( -7ba ) - a
    = 3ab - 9 - 7ba - a
    = 3ab - 7ba - a - 9
    = -4ab - a - 9
e. -3ab + 5bc - ( -2bc ) - ab
    = -3ab + 5bc + 2bc - ab
    = -3ab - ab + 5bc + 2bc
    = -4ab + 7bc